OHVIRA syndrome with Orofacial clefts: a rare association - ., Sambedna; Kumar, Amit; Agarwal, Mukta; Agrawal, Nimisha; Sinha, Sudwita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Obstucted hemivagina with ipsilateral renal anomaly (OHVIRA) syndrome or Herlyn-Werner-Wunderlich syndrome (HWW) is a rare congenital anomaly consist of uterus didelphys, obstructed hemivagina, and ipsilateral renal agenesis. We are reporting an adolescent girl with orofacial defect who presented with lower abdominal pain. She attained menarche 3 months earlier and had a regular menstrual cycle with cyclical abdominal pain. On abdominal examination a firm, mobile tender mass extending from left iliac fossa up to umbilicus (24 weeks size) was found. Lower border of mass could not be approached. Further evaluation with ultrasound showed enlarged uterus with collection with internal echoes and non-visualization of the left kidney. CECT showed absent left kidney and didelphys uterus with large left hematocolpometra with left complex adenexal cyst. Patient was posted for hematocolpos drainage and vaginoplasty. An unusual presentation of regular menstruation and nonspecific abdominal pain delays the diagnosis, which can lead to severe complications such as endometriosis and infertility.